Determining the activity of body meridians during static exercise - O.V. Musiyenko; N.P. Matsola; L. Mykhats (H.S. Skovoroda Kharkiv National Pedagogical University, 2019)
The purpose of the work was to determine the means of acupuncture diagnosis according to the method of J. Nakatani, the effect of performing physical exercises on the body on an example of a static exercise, which is performed similarly to the Padmasana (outside the Lotus of Hatha Yoga). Material and methods. Ten students of DDPU named after them were examined. Ivan Franko 18-20 years old, who possessed the perfect technique of performing the chosen static exercise. To determine the activity of the body's meridians, Ryodoraku's technique for V. Nakatani was used. The electric current was measured in representative biological active points of the twelve main meridians: lung (P), pericardial (MS), heart (C), lymphatic and immune systems (TR), thin (IG) and thick (GI) intestines, spleen and pancreas (R), liver (F), kidney (R), urinary (V) and biliary (VB) bladder and stomach (E) in order to determine the possibility of studying the effects of physical exercises on the body by acupuncture diagnostic methods. Measurement was used to perform the exercise, during and after the exercise in 6 minutes. Results Relevant changes in the electrical activity indices at representative points of the body's meridians during a selected static exercise were revealed. The increase in electrical activity in the body's meridians, which according to the literature, is responsible for the functions of the small and large intestines, the pancreas, the spleen, the liver, the gall bladder, the gonads, the kidneys, the adrenal glands. Also, this exercise causes a decrease in electrical activity at representative points of the respiratory system, the cardiovascular system, the urinary and gall bladder, and the stomach. Conclusion. It is shown that the use of technique method Ryodoraku for B. Nakatani measurement of meridians during static exercise is similar to posture "Padmasana" in the system Hatha_Yoga allows you to observe activation of body meridians, which, according to literature, are responsible for functions of the small and large intestines, pancreas, spleen, liver, gall bladder, gonads, kidneys, adrenal glands. It is possible to propose the use of a method for diagnosing the activity of the meridians to determine the effect of static exercises on the human body, along with other generally accepted scientific methods.